Inhibition of ZEB1-AS1 confers cisplatin sensitivity in breast cancer by promoting microRNA-129-5p-dependent ZEB1 downregulation - Gao, Jin (Cancer Cell Int, 2020)
BACKGROUND: Breast cancer is the leading cause of cancer-related mortality in women worldwide. Long non-coding RNAs (lncRNAs) are of critical importance in tumor drug resistance. Herein, this study aims to determine the roles of lncRNA ZEB1-AS1 in drug resistance of breast cancer involving microRNA-129-5p (miR-129-5p) and ZEB1. METHODS: Microarray-based gene expression profiling of breast cancer was conducted to identify the differentially expressed lncRNAs. ZEB1 expression was measured in adjacent and cancerous tissues. Next, MCF-7 and MDA-MB-231 cells were treated with a series of inhibitor, mimic or siRNA to clarify the roles of lncRNA ZEB1-AS1 and miR-129-5p in drug resistance of breast cancer. Then the target relationship of miR-129-5p with lncRNA ZEB1-AS1 and ZEB1 was verified. The expression patterns of miR-129-5p, lncRNA ZEB1-AS1, Bcl-2, MDR-1, ZEB1 and corresponding proteins were evaluated. Moreover, the apoptosis and drug resistance of MCF-7 cell were detected by CCK-8 and flow cytometry respectively. RESULTS: LncRNA ZEB1-AS1 was observed to be an upregulated lncRNA in breast cancer, and ZEB1 overexpression was noted in breast cancerous tissues. MiR-129-5p was revealed to specifically bind to both ZEB1 and lncRNA ZEB1-AS1. Moreover, the expression levels of ZEB1-AS1, ZEB1, Bcl-2, MDR-1, and corresponding proteins were decreased, but the expression of miR-129-5p was increased with transfection of miR-129-5p mimic and lncRNA ZEB1-AS1 siRNA. Besides, drug resistance to cisplatin was inhibited, and cell apoptosis was promoted in breast cancer after transfection of miR-129-5p mimic, lncRNA ZEB1-AS1 siRNA, and ZEB1 siRNA. CONCLUSION: In conclusion, the study provides evidence that lncRNA ZEB1-AS1 silencing protects against drug resistance in breast cancer by promoting miR-129-5p-dependent ZEB1 downregulation. It may serve as a novel therapeutic target in breast cancer treatment.